2019
DOI: 10.1186/s40545-019-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Access to and use of medicines in the Annapurna region of Western Nepal and possible impacting factors

Abstract: Improving access to medicines is a major healthcare challenge for low-income countries because the problem traverses health systems, society and multiple stakeholders. The Annapurna region of Nepal provides a valuable case study to investigate the interplay between medicines, society and health systems and their effects on access to and use of medicines. Government health facilities and international aid organizations provide some healthcare in the region, communities participate actively in healthcare organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The male and female ratio may indicate the dominancy of the male ethnomedicinal practitioners than female. Such type of trends was also reported in different ethnomedicinal studies [2,10,14,36] (Table 2). About 43% of the respondents were farmers and healers who had broad knowledge of ethno-medicine.…”
Section: Demographic Details Of Informantssupporting
confidence: 82%
See 1 more Smart Citation
“…The male and female ratio may indicate the dominancy of the male ethnomedicinal practitioners than female. Such type of trends was also reported in different ethnomedicinal studies [2,10,14,36] (Table 2). About 43% of the respondents were farmers and healers who had broad knowledge of ethno-medicine.…”
Section: Demographic Details Of Informantssupporting
confidence: 82%
“…A large number of animals are used as medicine under traditional systems such as Ayurveda, Unani, Homeopathy, and Tibetan traditional medicines [4][5][6]. Many studies have shown use of animals as medicine in Nepal [5,[7][8][9][10][11][12][13] including a few studies from Chitwan-Annapurna Landscape, but are mainly related to medicinal plants [14][15][16][17] and wild edible plants [18]. Chitwan-Annapurna Landscape lies in between Chitwan National Park in the south and Annapurna Conservation area in the north with high variation in elevation (150 m to 8000 m).…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent detection rates of pharmaceutical compounds in rural areas are potentially a factor of variable access to medicines across villages in the Annapurna region where factors such as distance to local health care facility and cost have been reported to impact patient access (Bhuvan et al 2019). Antibiotics are typically self-prescribed and can be purchased over the counter (Adhikari et al 2021);, however, limited availability of essential medicines outside of urban areas may also be a contributing factor to the lower concentrations detected in rural areas, as only 36.6% of users in health posts reported year-round availability of essential medicines in rural Nepal (Bhuvan et al 2015).…”
Section: Detection Of Pharmaceuticals Within Kathmandu City and The Annapurna Regionmentioning
confidence: 99%
“…In rural locations, contaminant loads are often lower due to reduced chemical activity; however, the deterioration of surface water quality parameters, including biological oxygen demand, dissolved oxygen, and total coliforms, have been reported in response to increasing urbanisation (Harada and Karn 2001). Human-use pharmaceuticals are widely used in both urban and rural settings with public health services delivered by tertiary hospitals in urban areas and via district hospitals, primary healthcare centres and health posts in rural areas (Bhuvan et al 2019;Rai et al 2001). Due to limited sewage connectivity, in Nepal, waste is commonly stored in a pit or used as a natural fertiliser, and wastewater is often recycled or used for irrigation thereby providing a means of pharmaceuticals to enter, and become omnipresent, in the environment across rural and urban settings.…”
mentioning
confidence: 99%